"You look great!": The effect of viewing appearance-related Instagram comments on women's body image. (December 2018) - Tiggemann, Marika; Barbato, Isabella
Highlights: Positive appearance comments on Instagram photos lead to greater body dissatisfaction. Appearance comments have no effect on state self-objectification. Trait self-objectification predicts increase in body dissatisfaction in response to viewing Instagram photos. Abstract: Instagram is an increasingly popular social networking site where users post and share photos. The aim of the present study was to experimentally investigate the effect of viewing appearance-related comments accompanying Instagram images on women's body image. Participants were 128 female undergraduate students who viewed a set of attractive images paired with a brief positive comment. For half the participants, comments were related to appearance; the other half viewed the same images with place-related comments. As predicted, exposure to appearance comments led to greater body dissatisfaction than exposure to place comments. There was no significant effect on state self-objectification, but trait self-objectification predicted increase in body dissatisfaction regardless of experimental condition. It was concluded that comments form an important and integral part of Instagram imagery, one that has implications for body image in its own right.